The Brazilian Society of Rheumatology guidelines for axial spondyloarthritis – 2019 - Gustavo Gomes Resende; Eduardo de Souza Meirelles; Cláudia Diniz Lopes Marques; Adriano Chiereghin; Andre Marun Lyrio; Antônio Carlos Ximenes; Carla Gonçalves Saad; Célio Roberto Gonçalves; Charles Lubianca Kohem; Cláudia Goldenstein Schainberg; Cristiano Barbosa Campanholo; Júlio Silvio de Sousa Bueno Filho; et al. (Advances in Rheumatology, 2020)
Abstract Spondyloarthritis is a group of chronic inflammatory systemic diseases characterized by axial and/or peripheral joints inflammation, as well as extra-articular manifestations. The classification axial spondyloarthritis is adopted when the spine and/or the sacroiliac joints are predominantly involved. This version of recommendations replaces the previous guidelines published in May 2013. A systematic literature review was performed, and two hundred thirty-seven studies were selected and used to formulate 29 recommendations answering 15 clinical questions, which were divided into four sections: diagnosis, non-pharmacological therapy, conventional drug therapy and biological therapy. For each recommendation the level of evidence supporting (highest available), the strength grade according to Oxford, and the degree of expert agreement (inter-rater reliability) is informed. These guidelines bring evidence-based information on clinical management of axial SpA patients, including, diagnosis, treatment, and prognosis.